Partial Protease Characterization, In Vitro Protein Digestibility And Utilization Of Dietary Soybean In Giant Freshwater Prawn, Macrobrachium Rosenbergii (De Man) - Chisty, Md. Ay Az Hasan (2005)
Biochemical assays and electrophoretical observations using SDS-PAGE was conducted for partial identification and characterization of proteases in the digestive system of giant freshwater prawn (Macrobrachium rosenbergii). pH optima of the crude enzyme extracts of prawn showed 3 peaks in activity at pH 3.0, 6.0 and 9.0. The acid proteinase and trypsin at pH 2.5 and 9.0 showed higher activity respectively at 3 and 5hrs after the last feeding. Presence of serine class proteinase was identified using PMSF that reduced 33% of the total proteolytic activity. Reduction in activity by 82% and 55% using specific inhibitors TLCK and TPCK confirmed the presence of trypsin and chymotrypsin respectively while EDTA reduced 34% activity resembles the presence of metallo-proteinase. Characterization of the alkaline proteinases by 12% SDS-PAGE, after incubation of extract with or without specific inhibitors, produced six active bands of 13 to 136 kDa molar mass. Two trypsin bands of 13 and 36 kDa, three chymotrypsin bands of 23, 47 and 73 kDa and one metallo-proteinase of 136 kDa were identified from zymogram. The results suggest that an acid protease responsible for the initial digestion of proteins and trypsin and chymotrypsin are the main enzymes responsible for the rest.